A numerical investigation on quasi-static configuration and nonlinear dynamic response characteristics of marine towing cable. (15th November 2021) - Guo, Li; Yuan, Yuchao; Tang, Wenyong; Xue, Hongxiang
Abstract: The towed seismic cable system is the main equipment of marine seismic exploration, which is a widely-used technique in oil and gas exploration. The towing cable connects the ship and the towed body, transmitting electricity and signals. The vibration of cable induced by the vortex shedding can affect the signal transmission and thus the exploration efficiency. This paper proposes a time-domain nonlinear numerical model to investigate the cable's dynamic response for deeper understanding the mechanism. A large amount of towing cases for a real-scale towing cable are designed. With the fundamental study on the quasi-static configuration, natural frequency and encountered speed of the cable, its nonlinear dynamic response characteristics are analyzed systematically. The overall dynamic response presents a mixture pattern of traveling wave and standing wave, and multi-modal participation can be readily captured. Besides, the variable cable weights, cable lengths, towing speeds and towed body weights all exert a significant impact on the Root Mean Square (RMS) displacement and excited frequency of the cable's vibration. Associated with VIV mechanism analysis, the response characteristics with different structural physical parameters and working condition parameters are explained reasonably. Highlights: A nonlinear numerical model is proposed to investigate response characteristics of marine towing cables. Quasi-static configuration and dynamic response characteristics under non-uniform flows are analyzed systematically. Working condition effect on configuration is significant, and interesting response characteristics are captured. Dynamic response characteristics under different parameters are explained reasonably with VIV mechanism analysis.